Effects of 4- and 8-h preexercise feedings on substrate use and performance - Flynn, M. G.; Michaud, T. J.; Rodriguez-Zayas, J.; Lambert, C. P.; Boone, J. B.; Moleski, R. W. (Journal of Applied Physiology, 1989)
Seven well-trained male cyclists were studied during 105 min of cycling (65% of maximal oxygen uptake) and a 15-min "performance ride" to compare the effects of 4- and 8-h preexercise carbohydrate (CHO) feedings on substrate use and performance. A high CHO meal was given 1) 4-h preexercise (M-4), 2) 8-h preexercise (M-8), 3) 4-h preexercise with CHO feedings during exercise (M-4CHO), and 4) 8-h preexercise with CHO feedings during exercise (M-8CHO). Blood samples were obtained at 0, 15, 60, 105, and 120 min and analyzed for lactate, glucose, insulin, and glycerol. Total work output during the performance ride was similar for the M-4 (217,893 +/- 13,348 N/m) and M-8 trials (216,542 +/- 13,905) and was somewhat higher for the M-4CHO (223,994 +/- 14,387) and M-8CHO (224,702 +/- 15,709) trials (P = 0.059, NS). Glucose was significantly elevated throughout exercise, and insulin levels were significantly elevated at 15 and 60 min during M-4CHO and M-8CHO compared with M-4 and M-8 trials. Glycerol levels were significantly lower during the CHO feeding trials compared with placebo and were not significantly different during exercise when the subject had fasted an additional 4 h. The results of this study suggest that when preexercise meals are ingested 4 or 8 h before submaximal cycling exercise, substrate use and performance are similar.